Factors influencing young urologists' productivity and academic career choice - Resorlu, Berkan; Silay, Mesrur Selcuk; Onem, Kadir; Bayrak, Omer; Sonbahar, Adil Emrah; Acar, Omer; Tandogdu, Zafer (Wichtig Publishing, 2016)
Objective: The objective of this study is to identify the variables that affect young urologists' productivity and academic career choice. Patients and methods: We have conducted an internet-based national survey for urologists randomly sampled from the database of Turkish Urological Association and 110 physicians completed this survey. Participants were asked to answer three-page questionnaire including 37 questions, which takes around 5 min to complete. Questionnaire was consisting of four main sections: 'demography', 'education', 'working conditions' and 'quality of life'. Results: Increased dedicated research time, being interested in an academic career, being Fellow of the European Board of Urology (FEBU), having English proficiency, and greater numbers of manuscript publication during residency were associated with increased productivity after residency (p = 0.001, p = 0.028, p = 0.046, p<0.001 and p<0.001, respectively). The remaining variables including age at marriage, age at having a child, monthly salary, length of residency, having a mentor or role model during residency showed no significant relationship with manuscript publications. Twenty-nine physicians (26.4%) stated that they had once been interested in their residency but were no longer interested in academic urology. Reasons for this loss of academic interest included lack of effective mentor or role model (27.2%), bureaucracy (17%), financial issues (13.6%), mandatory rule to work in public hospitals (18.2%) or military hospitals (9%) and language problems (21.6%). Conclusions: Our data indicate that increased time spent for research, being interested in an academic career, being an FEBU, having English proficiency, and greater publication during residency were associated with increased numbers of publications and academic career choice.
Keywords: Academic career; Productivity; Publication